LEFT BUNDLE-BRANCH BLOCK IMPACT ON ROTATIONAL MOTION OF LEFT VENTRICULAR WALLS IN PATIENTS WITH DILATED CARDIOMYOPATHY - Трембовецька О. М.; Книшов Г. В.; Захарова В. П. (World of Medicine and Biology, 2014)
Physiological processes of excitation, electromechanical coupling, contraction and relaxation of the heart are impossible without active energy cost. The effective performance of the left ventricular myocardium is determined not only by its contractive activity but, to a considerable degree, by the rotational component of the motion, which is the most effective and least energy-cost. However, this component of a complex biomechanics of the heart has little been studied, especially in dilated cardiomyopathy. Dilated cardiomyopathy is characterized by the considerable megalocardia due to manifested dilatation of the cardiac cavities and pronounced myocardial contractile failure, caused by the primary internal defect of the damaged cardiac hystiocytes. This is followed by progressive heart failure and poor prognosis. The purpose of the research is to study the features of the rotational motion of left ventricular walls in patients with dilated cardiomyopathy according to the occurrence or absence of the total left bundle-branch block. Object and Methods. 70 patients with dilated cardiomyopathy and 35 patients without cardiac pathology have been involved into study. Common laboratory methods of examination and complex echocardiography, including the Speckle-tracking echocardiography, have been carried out. Patients with dilated cardiomyopathy have been assigned to 2 groups, according to the stage of heart failure and occurrence of the total left bundle-branch block. Results and Discussion. Rising of end-diastolic and end-systolic indices, as well as lowering of heart beat index and ejection fraction, intensification of hypertension in the pulmonary artery and occurrence of moderate mitral and tricuspid regurgitation has been noted in patients with dilated cardiomyopathy. These changes worsen significantly in the occurrence of total left bundle-branch block. Normal left ventricular basal and apical rotation constituted -4,3 ± 1,30 , and 10,5 ± 0,60, respectively. Decrease of both basal rotation by 37% and apical rotation by 64%, as compared to normal rates, have been observed in Group I of patients with dilated cardiomyopathy. At the same time the basal and apical rotation was in the interreverse directions. Moderate decrease of basal rotation, constituting 2,6 ± 1,70, which is 40% lower the normal rates, have been observed in Group II of patients with dilated cardiomyopathy with total left bundle-branch block. At the same time the apical rotation was in the same direction as the basal one, with angle of rotation of -2,3 ± 1,50, which is significantly lower than normal rates by 122%. In dilated cardiomyopathy the rotational capacity of left ventricular myocardium is sharply decreased with the increase of signs of heart failure, and, additionally, in occurrence of total left bundle-branch block the direction of apical rotation changed.
Keywords: dilated cardiomyopathy; echocardiography; rotation; heart failure